Constructing and validating a scale for technostress and employee behavior: evidence from business schools in a developing country - Shan Cao; Sadaqat Ali; Rao Bakhat Yawar; Naveed Saif; Gerald Guan Gan Goh; Faheem Khan; Mudassir Hussain (BMC Psychology)
Abstract This research aimed to adapt and validate the Techno-Stress Construct in Higher Education (TCHS) for business school faculty in Pakistan. The study involved 300 faculty members from Khyber Paktunkhawa (KP) and Islamabad, who helped translate and adapt the TCHS into a 16-item Pakistani version. Exploratory Factor Analysis (EFA) and Confirmatory Factor Analysis (CFA) using AMOS 23 were employed to validate the factor structure. EFA identified four factors: techno-overload, techno-invasion, techno-complexity, and techno-uncertainty. CFA confirmed the structural model with excellent fit metrics. Reliability analysis showed strong Cronbach’s alpha coefficients for both total and subscale measurements. Construct validity tests indicated significant relationships between TCHS components and faculty emotional exhaustion, work-life balance, and commitment. The findings suggest that the adapted TCHS is a valid tool for identifying techno-stress among educators in Pakistan, which can aid in developing interventions to enhance faculty welfare and productivity. Future research should explore its applicability across different populations.